Peran Moderasi Religiusitas Terhadap Hubungan Antara Dimensi Fraud Pentagon Dengan Kecurangan Akademik - Lisda Ariani Simabur; Effendi M; Astri Dwi Jayanti Suhandoko; Zainuddin Zainuddin (Politeknik Ganesha Medan, 2023)
This study aims to determine and analyze the effect of the Pentagon dimension of fraud on academic fraud. The sample in this study was UPBJJ-UT Ternate students who were conducting lectures during the Covid-19 period as many as 134 respondents. The sampling technique in this study used a saturated sample. Methods of data collection using a questionnaire (questionnaire). Data analysis using path coefficient analysis with the help of the Smart PLS program. Based on the results of the research above, it can be concluded that 1) academic pressure affects academic fraud behavior; 2) opportunity does not affect academic fraud behavior; 3) rationalization affects academic fraud behavior; 4) the ability to influence academic fraud behavior; 5) personal ethics affect academic fraud behavior; Meanwhile, religiosity as a moderator does not affect the relationship between pressure, opportunity, rationalization, ability and personal ethics with academic fraud behavior. Although not large, based on the results of multi-group analysis, religiosity is proven to be moderate which will reduce the level of academic fraud. Religious students are more likely not to commit academic fraud, even though they are under pressure, have opportunities, rationalization, have abilities, and their ethics are still low. Efforts to prevent academic fraud that can be carried out at UPBJJ-UT Ternate include socialization activities that are classified as fraud and the sanctions, convincing students that fraud will be caught and will be announced, ensuring students are not in a situation where they work by fraud, showing evidence that all fraud is proven will be penalized, train students to be able to write without fraud and encourage students to have pride when acting under ethical teachings.